Khảo sát một số tính chất của màng phủ silica lai hữu cơ được chuẩn bị bằng phương pháp điện di lắng đọng - Sơn, Hà Hữu; Tú, Doãn Anh; Hùng, Nguyễn Đức (Vietnam Journal of Chemistry, 2015)
Hybrid silica coatings were developed on aluminum alloy by electrophoretic deposition method in the different conditions. The component of the coatings include polysiloxane network is tightly linked with the organic groups and additives. These components are tightly linked by chemical bonds. Corrosion resistance properties of the coatings were tested by potentiodynamic polarization curves. The results show that the corrosion current of hybrid coatings is the smallest when coating was deposited in optimal condition (C2 solution, iEPD = 1 mA/cm2 with a time of 20 minutes).  Corrosion currents of hybrid coating were 715 times smaller than that of bare sample. A heat treatment of less than 400 oC can be applied to the hybrid silica coatings without altering their organic groups. When the sintered temperature rises above 410 °C, the organic groups in the network will be decomposed violently and almost completely decomposed at 650 °C.